Spacefaring : the human dimension - Harrison, Albert A. (University of California Press, 2001)
The stars have always called us, but only for the past forty years or so have we been able to respond by traveling in space. This book explores the human side of spaceflight: why people are willing to brave danger and hardship to go into space; how human culture has shaped past and present missions; and the effects of space travel on health and well-being.